Endoscopic instrument tracking for surgical simulation training in a controlled environment via a camera and a planar mirror. (1st December 2015) - Dayak, Erdal; Çevik, Ulus
Abstract: Minimally Invasive Surgery (MIS) has many advantages over traditional procedures and thus training with MIS tools via computer simulations has received much attention. These tools are generally grouped into two major categories: Physical training-boxes, and Computer vision/Virtual Reality (VR) tools. In this study, a computer vision based simulator is proposed which uses a training box that is composed of a single camera and a planar mirror. Occlusions are appropriately handled by the use of the epipoint geometry. The average 3D positional error was 0.96 mm (±0.44 mm) at 1280×960 resolution, and 1.18 mm (±0.52 mm) at 320×240. So, the error is minimally affected as the resolution decreases. The proposed method has some advantages over relevant literature methods, such as an improved accuracy (approximately 60%) even at low resolutions with a low processing time (approximately 30%). Therefore, the proposed method appears as a promising and low cost (approximately 50%) alternative for computer vision based MIS training tools.